Immunogenic and efficacious SARS-CoV-2 vaccine based on resistin-trimerized spike antigen SmT1 and SLA archaeosome adjuvant - Bassel Akache (Nature Portfolio, 2021)
Abstract The huge worldwide demand for vaccines targeting SARS-CoV-2 has necessitated the continued development of novel improved formulations capable of reducing the burden of the COVID-19 pandemic. Herein, we evaluated novel protein subunit vaccine formulations containing a resistin-trimerized spike antigen, SmT1. When combined with sulfated lactosyl archaeol (SLA) archaeosome adjuvant, formulations induced robust antigen-specific humoral and cellular immune responses in mice. Antibodies had strong neutralizing activity, preventing viral spike binding and viral infection. In addition, the formulations were highly efficacious in a hamster challenge model reducing viral load and body weight loss even after a single vaccination. The antigen-specific antibodies generated by our vaccine formulations had stronger neutralizing activity than human convalescent plasma, neutralizing the spike proteins of the B.1.1.7 and B.1.351 variants of concern. As such, our SmT1 antigen along with SLA archaeosome adjuvant comprise a promising platform for the development of efficacious protein subunit vaccine formulations for SARS-CoV-2.